Active energy ray-curable composition, cured product thereof, and layered product
The active energy ray curable composition, incorporating urethane (meth)acrylate with farnesene units, addresses the challenge of achieving low viscosity and high performance in cured products, resulting in excellent transparency, flexibility, and heat resistance.
Patent Information
- Application Number
- JP2023171144
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-10-02
- Publication Date
- 2025-04-14
- Estimated Expiration
- 2043-10-02
AI Technical Summary
Existing curable compositions face challenges in achieving low viscosity while maintaining the flexibility and heat resistance of the cured products, particularly with hydrogenated polybutadiene polyol-based urethane (meth)acrylates and polypropylene glycol-based urethane (meth)acrylates.
An active energy ray curable composition containing urethane (meth)acrylate with structural units derived from farnesene, another (meth)acrylate, and a photopolymerization initiator, which allows for a low viscosity composition that produces cured products with excellent transparency, flexibility, and heat resistance.
The curable composition achieves a low viscosity while ensuring the cured product has excellent transparency, flexibility, and heat resistance, making it suitable for optical components and liquid gaskets.
Smart Images

Figure 2025062221000007 
Figure 2025062221000008 
Figure 2025062221000009
Abstract
Description
[Technical field]
[0001] The present invention relates to an active energy ray-curable composition, a cured product thereof, and a laminate. [Background technology]
[0002] In optical components such as displays for electronic devices, a transparent resin composition is filled between layers of a transparent substrate from the viewpoint of improving visibility. In addition, liquid gaskets are filled into joints of automobile parts and the like in order to fill gaps between parts, and transparent liquid gaskets are used from the viewpoint of visibility and appearance. For such resin compositions for optical components and liquid gaskets, resin materials that can form cured products that are excellent in flexibility and heat resistance in addition to transparency are required.
[0003] Patent Document 1 proposes a curable composition containing a hydrogenated polybutadiene polyol-based urethane (meth)acrylate as a highly transparent resin material (for example, Patent Document 1, etc.). Patent Document 2 proposes a curable composition containing a polypropylene glycol-based urethane (meth)acrylate. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2010-265402 A [Patent Document 2] International Publication No. 2009 / 142237 Summary of the Invention [Problem to be solved by the invention]
[0005] Hydrogenated polybutadiene polyol-based urethane (meth)acrylate has a high viscosity, and it is necessary to add a large amount of monomer to adjust the viscosity. If the amount of monomer is large, the cohesive force of the cured product is weakened and the flexibility of the obtained coating film is reduced. Therefore, it is difficult to obtain a curable composition with a low viscosity while maintaining the flexibility of the coating film.
[0006] On the other hand, polypropylene glycol-based urethane (meth)acrylates have a low viscosity and therefore require a small amount of monomer, but the heat resistance of the cured product is low.
[0007] An object of the present disclosure is to provide an active energy ray-curable composition which has a low viscosity and gives a cured product having excellent transparency, flexibility, and heat resistance, and a cured product thereof, and a laminate. [Means for solving the problem]
[0008] As a result of intensive investigations, the present inventors have found that the above-mentioned problems can be solved by an active energy ray-curable composition containing a urethane (meth)acrylate (X) containing a structural unit derived from farnesene, a (meth)acrylate (Y) other than the urethane (meth)acrylate (X), and a photopolymerization initiator (Z). Effect of the Invention
[0009] According to the present disclosure, it is possible to provide an active energy ray-curable composition that has a low viscosity and can give a cured product that is excellent in transparency, flexibility, and heat resistance, as well as a cured product thereof, and a laminate. [Brief description of the drawings]
[0010] [Figure 1] FIG. 2 is a schematic diagram showing a test piece for evaluating transparency in the examples. [Diagram 2] FIG. 2 is a top view of a laminate 20 for evaluating heat resistance in an example. [Diagram 3] FIG. 2 is a side view of a laminate 20 for evaluating heat resistance in an embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] Hereinafter, an embodiment of the present disclosure will be described in detail, but the scope of the present disclosure is not limited to the embodiment described here, and various modifications can be made within the scope of the present disclosure. Each aspect disclosed in this specification can be combined with any other feature disclosed in this specification. In addition, when multiple upper and lower limit values are described for a specific parameter, any upper and lower limit values among these upper and lower limit values can be combined to form a suitable numerical range. In addition, the lower and / or upper limit values of the numerical range described in this disclosure are numerical values within the numerical range and may be replaced with numerical values shown in the examples. The expression "1 to 10" indicating a numerical range means "1 or more and 10 or less". When a specific description described for one embodiment is also applicable to other embodiments, the description may be omitted in other embodiments.
[0012] The configurations and combinations thereof in each embodiment are merely examples, and addition, omission, substitution, and other modifications of the configurations are possible as appropriate without departing from the spirit of the present disclosure. The present disclosure is not limited to the embodiments.
[0013] Each feature disclosed herein may be combined with any other feature disclosed herein.
[0014] [Active energy ray-curable composition] A first embodiment of the present disclosure relates to an active energy ray-curable composition. The active energy ray curable composition according to the first embodiment includes a urethane (meth)acrylate (X) containing a structural unit derived from farnesene, a (meth)acrylate (Y) other than the urethane (meth)acrylate (X), and a photopolymerization initiator (Z). According to the active energy ray curable composition according to the first embodiment (hereinafter simply referred to as "curable composition"), a cured product having excellent transparency, flexibility, and heat resistance while having a low viscosity can be obtained.
[0015] The curable composition according to the first embodiment includes a urethane (meth)acrylate (X) (hereinafter, sometimes referred to as "(X) component") containing a structural unit derived from farnesene. The urethane (meth)acrylate (X) containing a structural unit derived from farnesene has a small molecular weight of the side chain and a small intermolecular interaction, and therefore is difficult to increase in viscosity. Therefore, a low-viscosity curable composition can be obtained with a small amount of monomer. Even more surprisingly, a curable composition having a low viscosity obtained by combining the (X) component with a (meth)acrylate (Y) (hereinafter, sometimes referred to as "(Y) component") other than the (X) component can obtain a cured product having excellent flexibility and heat resistance. In addition, the cured product obtained from such a curable composition containing the (X) component and the (Y) component also has good transparency.
[0016] <Urethane (meth)acrylate (X)> The curable composition according to the first embodiment includes the component (X). As described above, the component (X) is unlikely to become highly viscous due to its structure. The component (X) may be used alone or in combination of two or more kinds.
[0017] The (X) component is a compound containing a structural unit derived from farnesene, one or more urethane bonds, and one or more acryloyl groups. In one embodiment, the (X) component is preferably a compound containing a structural unit derived from farnesene, two or more urethane bonds, and one or less acryloyl groups.
[0018] (Physical Properties) ·viscosity In one embodiment, from the viewpoint of achieving a low viscosity of the curable composition, the viscosity of the component (X) at 60°C is preferably 10 to 10,000 mPa·s, more preferably 100 to 8,000 mPa·s, even more preferably 500 to 5,000 mPa·s, and particularly preferably 1,000 to 4,000 mPa·s. The viscosity of the component (X) can be measured at 60°C using an E-type viscometer (for example, product name "TV-25 Model" manufactured by Toki Sangyo Co., Ltd.).
[0019] ·Weight average molecular weight (Mw) In one embodiment, the weight average molecular weight (Mw) of the (X) component is preferably 5,000 to 30,000, more preferably 5,000 to 20,000, and even more preferably 8,000 to 18,000. When Mw is 5,000 or more, the flexibility of the cured product tends to be good. In addition, the amount of by-products produced during the production of the (X) component is reduced, and the appearance of the curable composition tends to be good. In addition, when Mw is 30,000 or less, deterioration of curability and change in shape (melt) due to a decrease in crosslink density are unlikely to occur. The "weight average molecular weight (Mw)" of the (X) component is a value calculated in terms of polystyrene measured by GPC, and specifically, is a value measured by the method described below. In one embodiment, the Mw of the (X) component may be greater than 12,000, greater than 12,000 and not greater than 30,000, or greater than 12,000 and not greater than 18,000. When the (X) component has an Mw of greater than 12,000, the appearance of the curable composition tends to be better, and the flexibility of the cured product tends to be better.
[0020] In one embodiment, the (X) component is preferably a reaction product of a polyol (A) containing a structural unit derived from farnesene, a polyisocyanate (B), and a (meth)acrylate (C) having a hydroxyl group. The (X) component may also be a reaction product of a urethane prepolymer having an isocyanate group, which is a reaction product of the polyol (A) containing a structural unit derived from farnesene and the polyisocyanate (B), and a (meth)acrylate (C) having a hydroxyl group. In addition, the component (X) may be a reaction product of a polyol (A) containing a structural unit derived from farnesene, a polyisocyanate (B), a (meth)acrylate having a hydroxyl group (C), and an alcohol having one hydroxyl group (D).
[0021] (Polyol (A)) Polyol (A) is a polyol containing a structural unit derived from farnesene. In the present disclosure, "polyol" refers to a compound having two or more hydroxyl groups in the structure. A preferred example of the polyol (A) is a diol containing a structural unit derived from α-farnesene and / or β-farnesene. From the viewpoint of ease of production, it is preferable to contain a structural unit derived from β-farnesene. Note that α-farnesene and β-farnesene may be used in combination.
[0022] The polyol (A) may contain structural units (other structural units) other than the structural units derived from farnesene. Examples of the other structural units include structural units derived from conjugated dienes having 12 or less carbon atoms. In a preferred embodiment, the polyol (A) may be a polyol containing structural units derived from farnesene and structural units derived from conjugated dienes having 12 or less carbon atoms.
[0023] The conjugated diene having 12 or less carbon atoms is not particularly limited, and examples thereof include butadiene, isoprene, 2,3-dimethyl-butadiene, 2-phenyl-butadiene, 1,3-pentadiene, 2-methyl-1,3-pentadiene, 1,3-hexadiene, 1,3-octadiene, 1,3-cyclohexadiene, 2-methyl-1,3-octadiene, 1,3,7-octatriene, myrcene, chloroprene, etc. These conjugated dienes may be used alone or in combination of two or more.
[0024] In one embodiment, the polyol (A) is preferably a diol represented by the following formula (1) or a diol obtained by reducing (hydrogenating) the diol, and more preferably a diol represented by the following formula (1).
[0025] [ka]
[0026] In the above formula (I), m and n each independently represent an integer of 1 to 7.
[0027] The polyol (A) represented by the above formula (I) is preferably a polyfarnesene glycol. As the polyfarnesene glycol, a commercially available product may be used, for example, the product name "KRASOL (registered trademark) F3000" manufactured by Cray Valley.
[0028] In one embodiment, the weight average molecular weight (Mw) of the polyol (A) is preferably 1,000 to 4,000, more preferably 1,000 to 3,000. When the Mw of the polyol (A) is 1,000 to 4,000, the Tg of the (X) component does not become too high, and the flexibility of the cured product tends to be good. In addition, the amount of by-products in the (X) component tends to be small. Furthermore, the compatibility of the (X) component with other components including the (Y) component is unlikely to deteriorate. The "weight average molecular weight (Mw)" of the polyol (A) is a value calculated in terms of polystyrene measured by GPC, specifically, a value measured by the method described below. In one embodiment, the Mw of the polyol (A) may be less than 2,000, or may be 1,000 or more and less than 2,000. When the Mw of the polyol (A) is less than 2,000, a (X) component having a lower viscosity is easily obtained, and the viscosity of the curable composition is easily adjusted.
[0029] (Other polyols) In one embodiment, the (X) component may contain a polyol other than the polyol (A) as a raw material. Examples of the other polyols include polyolefin polyols, hydrogenated polyolefin polyols, polyester polyols, trimethylolpropane, pentaerythritol, glycerin, and modified compounds thereof. From the viewpoint of easily obtaining a (X) component with a lower viscosity, it is preferable to contain only the polyol (A).
[0030] (Polyisocyanate (B)) In the present disclosure, the term "polyisocyanate" refers to a compound having two or more isocyanate groups in the structure. The polyisocyanate (B) is not particularly limited, and is preferably at least one diisocyanate selected from the group consisting of alicyclic diisocyanates, aliphatic diisocyanates having branched chains, and diisocyanate compounds obtained by hydrogenating aromatic diisocyanates. The alicyclic diisocyanate is not particularly limited, but examples thereof include isophorone diisocyanate. The branched chain aliphatic diisocyanate is not particularly limited, but examples thereof include 2,2,4-trimethylhexamethylene diisocyanate, 2,4,4-trimethylhexamethylene diisocyanate, and the like. The diisocyanate compound obtained by hydrogenating the aromatic isocyanates is not particularly limited, but examples thereof include hydrogenated xylylene diisocyanate, hydrogenated diphenylmethane diisocyanate, and the like.
[0031] ((Meth)acrylate having a hydroxyl group (C)) The (meth)acrylate (C) having a hydroxyl group (hereinafter, sometimes referred to as "(meth)acrylate (C)") is not particularly limited as long as it is a compound having one or more hydroxyl groups and one or more acryloyl groups. In one embodiment, a (meth)acrylate of an aliphatic alcohol is preferred, and from the viewpoint of good compatibility with the polyol (A), a monofunctional (meth)acrylate of an aliphatic alcohol having one hydroxyl group and one acryloyl group is particularly preferred. Preferred examples of such a (meth)acrylate (C) include, for example, 2-hydroxyethyl (meth)acrylate, 3-hydroxy-n-propyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate. The (meth)acrylate (C) having a hydroxyl group may be used alone or in combination of two or more.
[0032] (Alcohol having one hydroxyl group (D)) In one embodiment, the (X) component may contain an alcohol (D) having one hydroxyl group (hereinafter, sometimes referred to as "alcohol (D)") as a raw material. By containing the alcohol (D) as a raw material, as described later, it becomes easier to adjust the acryloyl group concentration of the (X) component. Examples of such alcohol (D) include aliphatic or alicyclic primary alcohols having 3 or more carbon atoms, and the molecular weight thereof is preferably 70 to 400. If the alcohol (D) has 3 or more carbon atoms or a molecular weight of 70 or more, it is preferable because it is less likely to volatilize during the synthesis of the (X) component. In addition, if the molecular weight is 400 or less, the reactivity with the polyisocyanate (B) is less likely to decrease, and the production time is not too long. In addition, if the alcohol is an aliphatic or alicyclic alcohol, the hue of the (X) component is not too high, and the weather resistance is also likely to be good. Specific examples include 1-butanol, 1-heptanol, 1-hexanol, normal octyl alcohol, 2-ethylhexyl alcohol, cyclohexanemethanol, capryl alcohol, lauryl alcohol, myristyl alcohol, cetyl alcohol (cetanol), stearyl alcohol, and mixtures thereof. Among these, 2-ethylhexyl alcohol is preferred from the viewpoints of boiling point, price, and availability. The alcohol (D) may be used alone or in combination of two or more kinds.
[0033] <Method for producing urethane (meth)acrylate (X)> The method for producing the component (X) includes reacting (urethanization reaction) a polyol (A), a polyisocyanate (B), and a (meth)acrylate (C). The reaction method is not particularly limited, but in one embodiment, a method is preferred in which a polyol (A) is reacted with a polyisocyanate (B) to prepare a urethane isocyanate prepolymer (step (1)), and then the urethane isocyanate prepolymer is reacted with a (meth)acrylate (C) (step (2)) to obtain the component (X). When reacting the urethane isocyanate prepolymer with the (meth)acrylate (C), the (meth)acrylate (C) may be used in combination with an alcohol (D).
[0034] (Process (1)) Step (1) is more likely to prevent an increase in viscosity, improve the appearance of the component (X), suppress the production of by-products, and improve the transparency and heat resistance of the cured product, as compared to conventional production methods such as "a method of mixing and reacting polyol (A), polyisocyanate (B), and (meth)acrylate (C), or (A) to (C) and alcohol (D) all at once" or "a method of reacting polyisocyanate (B), (meth)acrylate (C), and alcohol (D) to form a urethane isocyanate prepolymer containing an isocyanate group, and then reacting the prepolymer with polyol (A)."
[0035] Specifically, when the composition is produced by "a method of mixing polyol (A), polyisocyanate (B), and (meth)acrylate (C), or (A) to (C) and alcohol (D) all at once and reacting them," the resulting component (X) tends to have a high viscosity. As a result, it is necessary to add a large amount of monomer to adjust the viscosity of the curable composition. In addition, stirring becomes difficult or the reaction proceeds unevenly, and the probability of partial gelation tends to increase. In addition, the amount of by-products of compounds that do not have polyol (A) in the skeleton tends to increase, and transparency and flexibility tend to decrease. In addition, since various complex compounds are easily generated irregularly, it is difficult to control the quality of the curable composition containing the component (X).
[0036] In the case of "a method in which a polyisocyanate (B) is reacted with a (meth)acrylate (C) and an alcohol (D) to form a urethane isocyanate prepolymer containing an isocyanate group, and then the prepolymer is reacted with a polyol (A)", a compound in which all of the isocyanate groups of the polyisocyanate (B) have reacted with the (meth)acrylate (C) or the alcohol (D) is easily produced as a by-product. This by-product exhibits crystallinity because it does not contain a polyol (A) skeleton, and as a result, transparency is easily reduced and the possibility of gelation is also increased.
[0037] From the above viewpoints, a method is preferred in which a polyol (A) is reacted with a polyisocyanate (B) to form a urethane isocyanate prepolymer, and then the urethane isocyanate prepolymer is reacted with a (meth)acrylate (C). That is, the following methods 1 to 3 can be further mentioned as methods that can be adopted in the step (1). [Method 1] Polyol (A) and polyisocyanate (B) are mixed together and reacted. [Method 2] A method in which polyol (A) is added dropwise to polyisocyanate (B) while reacting them. [Method 3] A method in which polyisocyanate (B) is added dropwise to polyol (A) to cause a reaction.
[0038] In the case of [Method 3], polyisocyanate (B) is dropped into a large amount of polyol (A) while reacting, and the isocyanate groups on both sides of polyisocyanate (B) are urethane-formed with the hydroxyl groups of 2 moles of polyol (A), and a diol having hydroxyl groups at both ends, which is an ABA type, is easily produced as a by-product. When 2 moles of polyisocyanate (B) are further reacted with the diol, a compound having isocyanate groups at both ends, which is an BABAB type, is easily produced as a by-product. When the same reaction is repeated, a large amount of a compound having the following structure, which is an ABA type, is easily produced as a by-product. B-[AB]nAB (n = an integer equal to or greater than 1) If a urethane prepolymer containing a large amount of such by-products is reacted with a (meth)acrylate (C) and an alcohol (D), the acrylic density of the resulting component (X) will be low, making it difficult for the cured product to achieve sufficient crosslink density. Therefore, from the viewpoint of easily obtaining a cured product having excellent flexibility and heat resistance, it is preferable to synthesize the urethane isocyanate prepolymer by [Method 1] or [Method 2].
[0039] A preferred method for producing a urethane isocyanate prepolymer by [Method 1] is as follows. The polyol (A) is first charged into the reactor and stirred until it becomes uniform, and then the polyisocyanate (B) is further charged and made uniform. When preparing the (X) component having a relatively large Mw, the (meth)acrylate (Y) may be added as a diluent to the polyol (A), and the polyol (A) and (Y) components may be stirred until they become uniform, and then the polyisocyanate (B) may be charged. This makes it possible to keep the viscosity of the reaction liquid low. After that, it is desirable to start the urethanization by adding a urethanization catalyst after increasing the temperature as necessary while stirring. After the urethanization catalyst is added, the temperature may be increased as necessary.
[0040] If the urethane-forming catalyst is added from the beginning before the polyol (A) and the polyisocyanate (B) become uniform, the urethane-forming reaction will proceed in a non-uniform state between the polyol (A) and the polyisocyanate (B) at the stage of charging the polyisocyanate (B), causing changes in the molecular weight and viscosity of the resulting urethane prepolymer, and the reaction may terminate with unreacted polyisocyanate (B) remaining in the system. In such a case, the (meth)acrylate (C) and alcohol (D) used later will react with the remaining polyisocyanate (B), making it easy for by-products to be produced, and the transmittance of the resulting cured product is likely to be low.
[0041] In one embodiment, the content of the by-products as described above in the component (X) is preferably less than 7% by weight based on the total weight of the component (X). If the content of the by-products is less than 7% by weight, the transparency of the cured product tends to be good.
[0042] [Method 1] is preferable in that when the highly viscous polyol (A) or the polyisocyanate (B) is a solid, these raw materials can be charged directly into the reactor, and that the component (X) can be produced in one pot.
[0043] A preferred method for producing a urethane isocyanate prepolymer by [Method 2] is as follows. A reactor is charged with polyisocyanate (B), a urethane catalyst, and, if necessary, a part of (meth)acrylate (Y), and stirred until homogeneous. While stirring, the temperature is raised if necessary, and the homogeneous mixture of polyol (A) and (meth)acrylate (Y) is added dropwise to react them. [Method 2] is a method suitable for the case where the polyol (A) has a high viscosity. A homogeneous mixture of the polyol (A) and the (meth)acrylate (Y) is prepared to have a low viscosity, and this mixture is then added dropwise to the polyisocyanate (B), which makes it difficult for the by-products described in [Method 3] to be produced.
[0044] In either method, the reaction in step (1) is preferably carried out until all hydroxyl groups are urethane-converted. The end point of the reaction can be confirmed by measuring the isocyanate group concentration (hereinafter also referred to as "NCO group concentration") in the reaction solution, and confirming that the isocyanate group concentration is equal to or lower than the isocyanate group concentration (theoretical NCO concentration) when all hydroxyl groups charged in the system are urethane-converted, or that the isocyanate group concentration no longer changes.
[0045] In one embodiment, the molar ratio of the isocyanate groups of the polyisocyanate (B) relative to 1 mole of the hydroxyl groups of the polyol (A) is preferably from 1.1 to 2.0 moles, more preferably from 1.1 to 1.6 moles.
[0046] In one embodiment, the step (1) is preferably carried out in the presence of a polymerization inhibitor. Preferred examples of the polymerization inhibitor include dibutylhydroxytoluene, hydroquinone, hydroquinone monomethyl ether, and phenothiazine. These may be used alone or in combination of two or more. The amount of these polymerization inhibitors added is preferably 1 to 10,000 ppm (by weight) relative to the obtained component (X), more preferably 100 to 1,000 ppm, and even more preferably 400 to 1,000 ppm. If the amount of the polymerization inhibitor added is within the above range, a sufficient polymerization inhibition effect is easily obtained and the physical properties of the component (X) are not adversely affected.
[0047] (Process (2)) The urethane isocyanate prepolymer obtained in the above step (1) is reacted with a (meth)acrylate (C) (in one embodiment, the (meth)acrylate (C) and an alcohol (D)) to obtain the component (X). If a large amount of unreacted isocyanate groups remain in the reaction liquid at this time, problems such as gelation or poor curing of the coating film may occur. To avoid these problems, it is preferable that in step (2), the reaction is carried out so that the number of moles of hydroxyl groups in the (meth)acrylate (C) is in excess relative to the number of moles of isocyanate groups in the urethane isocyanate prepolymer, and the reaction is continued until the concentration of residual isocyanate groups in the reaction solution reaches 0.05% by weight or less. In the reaction, the number of moles of hydroxyl groups in the (meth)acrylate (C) relative to 1 mole of isocyanate groups in the urethane isocyanate prepolymer is preferably 1.005 to 1.1 moles, more preferably 1.01 to 1.05. In one embodiment, the molar ratio ((B):(C)) of the polyisocyanate (B) to the (meth)acrylate (C) may be 3.00:2.00 to 3.00:2.09.
[0048] For the same purpose, the production of component (X) is preferably carried out in an atmosphere of a molecular oxygen-containing gas, the oxygen concentration being appropriately selected taking safety into consideration.
[0049] In one embodiment, a catalyst (urethanization catalyst) may be used to obtain a sufficient reaction rate. As the catalyst, dibutyltin dilaurate, tin octylate, tin chloride, bismuth neodecanoate (III), bismuth 2-ethylhexanoate (III), zinc neodecanoate, zinc octylate, etc. may be used, but dibutyltin dilaurate is preferred from the viewpoint of reaction rate. The amount of these catalysts added is usually preferably 1 to 3,000 ppm (by weight) relative to the obtained component (X), more preferably 50 to 1,000 ppm. If the amount of catalyst added is within the above range, a sufficient reaction rate is easily obtained and the physical properties of the component (X) are not adversely affected.
[0050] The production of the (X) component can be carried out in the presence of a known volatile organic solvent. The volatile organic solvent can be distilled off under reduced pressure after the production of the (X) component. In addition, the volatile organic solvent remaining in the active energy ray curable resin composition can be applied to a transparent substrate and then removed by drying. The volatile organic solvent means an organic solvent having a boiling point not exceeding 200°C.
[0051] In one embodiment, when applied to a field where curing is performed in a sealed state, it is preferable that volatile organic solvents are not substantially used from the time of producing the (X) component to the preparation of the final curable composition. That is, when applied to such a field, the ratio of volatile organic solvents contained in the curable composition according to the first embodiment is preferably 0.5 wt % or less, more preferably 0.1 wt % or less, based on the total weight of the curable composition.
[0052] In one embodiment, the reaction temperature in step (1) and / or step (2) is preferably 130° C. or lower, more preferably 40 to 130° C. If the reaction temperature is within the above range, it is easy to suppress the generation of gelled matter while maintaining a practically sufficient reaction rate.
[0053] It is preferable to carry out the step (2) until the concentration of the residual isocyanate group becomes 0.1% by weight or less. The concentration of the residual isocyanate group can be analyzed by gas chromatography, titration method, or the like.
[0054] In one embodiment, the acryloyl group concentration in the component (X), calculated from the following formula (3), is preferably 0.10 mol / kg or more and less than 1.0 mol / kg, and more preferably 0.2 mol / kg or more and less than 0.60 mol / kg. Acryloyl group concentration (mol / kg) = weight of (meth)acrylate (C) (g) × number of (meth)acryloyl groups in (meth)acrylate (C) molecule ÷ molecular weight of (meth)acrylate (C) × 1000 ÷ weight of component (X) (g) (3) Here, the number of acryloyl groups in the (meth)acrylate (C) is, for example, 1 in the case of 2-hydroxyethyl acrylate, and 3 in the case of pentaerythritol triacrylate.
[0055] If the acryloyl group concentration is 0.10 mol / kg or more, the composition is easily cured sufficiently when irradiated with active energy rays, and the cohesive force is not easily decreased, and the initial adhesion to the substrate is not easily decreased. If the concentration is less than 1.0 mol / kg, the heat resistance of the resulting cured product is not easily decreased. In the present disclosure, "excellent heat resistance" means that when the cured product is stored under conditions of 95°C and 1000 hours, the coating film hardness does not increase, the adhesion to the substrate is not decreased, and the curing shrinkage is not caused, resulting in a change in the shape of the coating film. That is, from the viewpoint of improving the heat resistance of the resulting cured product, it is effective to keep the acryloyl group concentration in the (X) component low and reduce the curing shrinkage. However, in this case, the coating film hardness is decreased, and the adhesion to the substrate is easily decreased. In one embodiment, from the viewpoint of preventing a decrease in coating hardness while keeping the acryloyl group concentration of component (X) low (preferably less than 1.0 mol / kg), the aforementioned alcohol (D) may be reacted with component (X) to alkoxylate some of the terminal acryloyl groups of component (X).
[0056] <(Meth)acrylate (Y)> The curable composition according to the first embodiment contains a (meth)acrylate (Y) other than the component (X). The component (Y) is selected from the viewpoint of adjusting the viscosity of the curable composition and various physical properties of the cured product. In one embodiment, from the viewpoint of easily improving viscosity adjustment, the appearance of the curable composition, suppression of by-products, and transparency and heat resistance of the cured product, it is preferable that the (Y) component contains a monofunctional (meth)acrylate.
[0057] As monofunctional (meth)acrylates, from the viewpoint of ease of adjusting the viscosity and various physical properties of the cured product, methyl (meth)acrylate, ethyl (meth)acrylate, glycerin mono(meth)acrylate, glycidyl (meth)acrylate, dicyclopentenyl (meth)acrylate, n-butyl (meth)acrylate, β-carboxyethyl (meth)acrylate, isobornyl (meth)acrylate, octyl / decyl (meth)acrylate (mixture of octyl (meth)acrylate and decyl (meth)acrylate) are preferred. Examples of the acrylates include acrylates (meth)acrylates), n-octyl (meth)acrylate, isooctyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, isodecyl (meth)acrylate, n-lauryl (meth)acrylate, n-stearyl (meth)acrylate, cyclohexyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, and β-carboxyethyl acrylate. These may be used alone or in combination of two or more. Among these, from the viewpoint of high dilution efficiency and easy viscosity adjustment of the curable composition, aliphatic (meth)acrylates having an alkyl group with 1 to 15 carbon atoms are preferred, n-octyl (meth)acrylate and octyl / decyl (meth)acrylate are more preferred, and n-octyl acrylate (NOA) is even more preferred. From the viewpoint of easily improving the toughness and extensibility of the cured product, alicyclic (meth)acrylates are preferred, isobornyl (meth)acrylate is more preferred, and isobornyl acrylate (IBOA) is even more preferred. In one embodiment, the (Y) component may contain one or more selected from n-octyl acrylate (NOA), isobornyl acrylate (IBOA), and octyl / decyl (meth)acrylate.
[0058] The curable composition according to the first embodiment can achieve a low viscosity at least when the amount of the (Y) component is at least 600 mPa·s. In one embodiment, the viscosity of the curable composition at 25° C. may be 600 mPa·s or less. In addition, the content of the (Y) component in the curable composition at this time is preferably 90% by weight or less with respect to the total weight of the curable composition. In one embodiment, the ratio of the (Y) component to the total weight of the curable composition may be 60% by weight or less, or may be 55% by weight or less. In one embodiment, when the (Y) component contains at least one selected from NOA and IBOA, the ratio of the (Y) component to the total weight of the curable composition having the above-mentioned viscosity may be 20 to 55% by weight, or may be 25 to 55% by weight.
[0059] <Photopolymerization initiator (Z)> The curable composition according to the first embodiment contains a photopolymerization initiator (Z) (hereinafter, may be referred to as "component (Z)"). As the component (Z), a known photoradical polymerization initiator or photocationic polymerization initiator can be used depending on the type of active energy ray and the component (X). Examples of the (Z) component include 1-hydroxycyclohexyl phenyl ketone, 2-hydroxy-2-methyl-1-phenylpropan-1-one, diethoxyacetophenone, 1-(4-isopropylphenyl)-2-hydroxy-2-methylpropan-1-one, 1-(4-dodecylphenyl)-2-hydroxy-2-methylpropan-1-one, 4-(2-hydroxyethoxy)-phenyl(2-hydroxy-2-propyl)ketone, 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinopropane-1, benzoin, benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, benzoin n-butyl ether, benzoin phenyl ether, and benzoin. Examples of the (Z) component include dimethyl ketal, benzophenone, benzoylbenzoic acid, methyl benzoylbenzoate, 4-phenylbenzophenone, hydroxybenzophenone, acrylated benzophenone, 4-benzoyl-4'-methyldiphenyl sulfide, 3,3'-dimethyl-4-methoxybenzophenone, thioxanthone, 2-chlorothioxanthone, 2-methylthioxanthone, 2,4-dimethylthioxanthone, isopropylthioxanthone, 2,4-dichlorothioxanthone, 2,4-diethylthioxanthone, 2,4-diisopropylthioxanthone, 2,4,6-trimethylbenzoyldiphenylphosphine oxide, methylphenyl glyoxylate, benzyl, camphorquinone, etc. These (Z) components may be used alone or in combination of two or more.
[0060] The content of the (Z) component is not particularly limited. In one embodiment, the content is preferably 1 to 20 parts by weight, more preferably 1 to 5 parts by weight, relative to 100 parts by weight of the total of the (X) component and the (Y) component. If the content of the (Z) component is within the above range, curing failure is unlikely to occur, and a curable composition with little odor derived from the (Z) component is likely to be obtained.
[0061] <Additives> The curable composition according to the first embodiment may contain various additives as necessary. Examples of such additives include organic and / or inorganic fillers, dyes and pigments, leveling agents, ultraviolet absorbers, light stabilizers, antifoaming agents, dispersants, and thixotropic agents. The content of these additives is not particularly limited, and may be, for example, 0 to 10 parts by weight, or 0.05 to 5 parts by weight, relative to 100 parts by weight of the curable composition.
[0062] As described above, the curable composition according to the first embodiment has a low viscosity, and can give a cured product that is excellent in transparency, heat resistance, and flexibility. In one embodiment, the cured product obtained by curing the curable composition under the following conditions preferably has a transmittance of 95% or more at a wavelength of 400 nm. (Ultraviolet irradiation conditions) Irradiation intensity: 120W / cm Irradiation distance: 10cm Conveyor speed: 5m / min Number of exposures: 2
[0063] <Method of producing curable composition> The curable composition according to the first embodiment can be produced by mixing the above-mentioned components (X) to (Z) with the above-mentioned additives. As a mixing means, known or conventional means, for example, various mixers such as dissolvers and homogenizers, kneaders, rolls, bead mills, and self-revolving stirrers, can be used. Conditions such as temperature and rotation speed during mixing are not particularly limited and can be appropriately set. In one embodiment, the method for producing the curable composition may include blending the (Y) component with the (X) component to obtain a viscosity adjusting liquid, and blending the (Z) component with the viscosity adjusting liquid to obtain the curable composition.
[0064] <Uses of the curable composition> The curable composition according to the first embodiment is characterized in that the viscosity is low at least when the amount of the (Y) component is included. Furthermore, the curable composition gives a cured product having excellent transparency, flexibility and heat resistance. Such a curable composition can be suitably used, for example, as a curable composition for optical members or liquid gaskets. It should be noted that the use of the curable composition is not limited to these optical members and liquid gaskets.
[0065] [Cured product] The second embodiment of the present disclosure is a cured product of the curable composition according to the first embodiment. The curable composition according to the first embodiment can be cured by irradiation with active energy rays. The cured product according to the second embodiment includes both the above-mentioned curable composition irradiated with active energy rays to promote the curing reaction, and the cured product completely cured by irradiation with active energy rays. In addition, the cured product of this embodiment also includes a "semi-cured product" in which the curable composition has been cured to such an extent that it no longer has fluidity.
[0066] The cured product according to the second embodiment can be obtained as a cured coating film, for example, by applying the curable composition according to the first embodiment to an object such as a substrate, and then irradiating the cured composition with active energy rays.
[0067] The method for applying the curable composition is not particularly limited, and a conventionally known method can be adopted, for example, a spraying method, an airless spray method, an air spray method, a roll coating method, a bar coating method, a gravure method, etc. can be used. Among them, the roll coating method is most preferably used from the viewpoints of aesthetics, cost, workability, etc. The application of the curable composition may be a so-called in-line coating method, which is performed during the manufacturing process of a plastic film, etc., or a so-called offline coating method, which is performed in a separate process on an already manufactured substrate. From the viewpoint of production efficiency, the offline coating method is preferred.
[0068] <Active energy rays> Examples of the active energy rays include ultraviolet rays and electron beams. Examples of light sources used for ultraviolet irradiation include high-pressure mercury lamps, ultra-high-pressure mercury lamps, carbon arc lamps, xenon lamps, and metal halide lamps. The irradiation time varies depending on the type of light source, the distance between the light source and the coating surface, and other conditions, but is at most several tens of seconds, and is usually several seconds. Usually, an irradiation source with a lamp output of about 80 to 300 W / cm is used. In the case of electron beam irradiation, it is preferable to use electron beams having an energy in the range of 50 to 1000 KeV and an irradiation dose of 2 to 5 Mrad. After irradiation with active energy rays, heating may be performed as necessary to promote curing.
[0069] The thickness of the cured coating film is not particularly limited and can be adjusted as desired depending on the application, for example, in the range of 0.5 to 1,000 μm, preferably 2 to 500 μm.
[0070] The object (subject to be coated) to which the curable composition is applied is not particularly limited, and examples thereof include various articles such as plastic articles, articles whose plastic surfaces are subjected to metal deposition, glass, wood, metal plates, and paper. The coated surface may be subjected to a release treatment. When the curable composition according to the first embodiment is used for optical members, particularly as an interlayer filler for a transparent substrate (curable composition for interlayer filling), it is preferable to apply the composition to a transparent substrate. Details of the transparent substrate will be described later.
[0071] [Laminate] The third embodiment of the present disclosure is a laminate comprising a layer containing one or more selected from the curable composition according to the first embodiment and the cured product according to the second embodiment. In one embodiment, the laminate may comprise a layer containing one or more selected from the curable composition according to the first embodiment and the cured product according to the second embodiment, and two or more transparent substrates. In addition, a layer containing one or more selected from the curable composition according to the first embodiment and the cured product according to the second embodiment may be provided between the two or more transparent substrates.
[0072] <Transparent base material> When the laminate comprises a transparent substrate, the transparent substrate may be a glass substrate such as a transparent glass plate, or a plastic substrate such as a transparent plastic film.
[0073] The plastic substrate can be any existing transparent material, and is not particularly limited, but examples thereof include polyolefin resins such as polyethylene, ethylene-propylene copolymer, and ethylene-vinyl acetate copolymer, polyester resins such as polyethylene terephthalate, polyethylene naphthalate, and polybutylene terephthalate, acrylic resins, polycarbonate resins, etc. Among these, polycarbonate resins and acrylic resins are particularly preferably used.
[0074] <Method of manufacturing laminate> The method for producing the laminate according to the third embodiment includes a method including coating the curable composition according to the first embodiment on one or more substrates. In one embodiment, the method may include irradiating the curable composition with active energy rays after coating the curable composition. In addition, when the above-mentioned transparent substrate is used as the substrate, the method may include irradiating the curable composition with active energy rays from the transparent substrate side. As the coating method of the curable composition and the active energy rays, those described in the section on the cured product can be preferably adopted.
[0075] In one embodiment, the method for producing a laminate according to the third embodiment may include injecting the curable composition according to the first embodiment between two or more transparent substrates. After the injection, the method may include irradiating the transparent substrate with active energy rays. In this case, it is preferable to use a cartridge in order to prevent the generation of bubbles.
[0076] In the laminate, the thickness of the layer containing one or more selected from the curable composition according to the first embodiment and the cured product according to the second embodiment is preferably 30 to 300 μm, more preferably 50 to 200 μm. If the layer thickness is within the above range, the cost is not too high and the layer thickness is likely to be uniform. In addition, the flexibility is likely to be good. EXAMPLES
[0077] The present invention will be described in more detail below based on Synthesis Examples and Examples, but the present invention is not limited to these Examples in any way.
[0078] Synthesis examples and comparative synthesis examples are described below. The concentration notations "ppm" and "wt%" are concentrations relative to the (theoretically) obtained urethane (meth)acrylate (X) unless otherwise specified. In addition, methods for measuring the isocyanate group concentration, viscosity, and weight average molecular weight are described.
[0079] (Measurement of isocyanate group concentration) The isocyanate group concentration was measured as follows: The measurement was carried out in a 100 mL glass flask with stirring using a stirrer. Blank value measurement 15 mL of dibutylamine THF solution (0.1N) was added to 15 mL of THF, and 3 drops of bromophenol blue (1% methanol dilution) were added to color it blue. Then, titration was performed with an aqueous HCl solution with a normality of 0.1N. The titration volume of the aqueous HCl solution at the point when color change was observed was defined as Vb (mL). Measurement of actual isocyanate group concentration A sample was weighed out (Ws (g)) and dissolved in 15 mL of THF, and 15 mL of a dibutylamine THF solution (0.1N) was added. After confirming that the solution had been dissolved, three drops of bromophenol blue (1% methanol diluted solution) were added to color the sample blue. The sample was then titrated with an aqueous HCl solution with a normality of 0.1N. The titration volume of the aqueous HCl solution at the point when a color change was observed was recorded as Vs (mL). The isocyanate group concentration in the sample was calculated using the following formula. Isocyanate group concentration (weight%) = (Vb - Vs) x 1.005 x 0.42 ÷ Ws
[0080] (Method of measuring viscosity) · Urethane (meth)acrylate (X) The viscosity of the urethane (meth)acrylate (X) was measured at 60° C. using an E-type viscometer (manufactured by Toki Sangyo Co., Ltd., product name "TV-25 Model"). ·Curable composition The viscosity of the curable composition was measured at 25° C. using an E-type viscometer (manufactured by Toki Sangyo Co., Ltd., product name "TV-25 Model").
[0081] (Weight average molecular weight (Mw)) The weight average molecular weight was determined by GPC (gel permeation gas chromatography) under the following measurement conditions using standard polystyrene as the standard. Equipment used: High-speed GPC device (Tosoh Corporation, product name "HLC-8220GPC") Pump: DP-8020 Detector: RI-8020 Column type: Super HZM-M, Super HZ4000, Super HZ3000, Super HZ2000 Solvent: Tetrahydrofuran Phase flow rate: 1mL / min Column pressure: 5.0MPa Column temperature: 40℃ Sample injection volume: 10μL Sample concentration: 0.2mg / mL
[0082] <Material> The materials used in the examples and comparative examples are as follows. Polyol (A) (A1): Polyfarnesene glycol (manufactured by Cray Valley, product name "KRASOL F3000" (Mw: 1488, hydroxyl value: 0.672 mmoL / g, non-volatile content: 99.91%). Polyol (A') (A'1): Polypropylene glycol (manufactured by Sanyo Chemical Industries, Ltd., product name "Sannyx (registered trademark) PT2001", Mw: 1964, hydroxyl value: 57.1 mgKOH / g). (A'2): Polyester polyol (manufactured by Mitsui Chemicals, Inc., product name "Takelac (registered trademark) U2710", Mw: 988, hydroxyl value: 113.5 mgKOH / g). (A'3): Hydrogenated polybutadiene glycol (manufactured by Nippon Soda Co., Ltd., product name "NISSO PB GI3000" (Mw: 3965, hydroxyl value: 28.3 mg KOH / g). The Mw of the polyol (A) and the polyol (A') is a value calculated from the following formula (4) or (5) based on the hydroxyl value. Mw = 56.1 ÷ hydroxyl value (mgKOH / g) × 2,000 (4) Mw = 2,000 ÷ hydroxyl number (mmoL / g) (5)
[0083] Polyisocyanate (B) (B1): Isophorone diisocyanate (IPDI) (manufactured by Evonik Corporation, product name "VESTANAT (registered trademark) IPDI", Mw: 222). (B2): Hexamethylene diisocyanate (HDI) (manufactured by Tosoh Corporation, product name "HDI", Mw: 168). (B3): 2,2,4-trimethylhexamethylene diisocyanate (TMHDI) (manufactured by Evonik Corporation, product name "TMDI", Mw: 210). (B4): Diphenylmethane diisocyanate (MDI) (manufactured by Tosoh Corporation, product name "MDI", Mw: 250). (B5): methylene bis(4-cyclohexyl isocyanate) (hydrogenated MDI) (manufactured by Evonik Corporation, product name "DESMODUR (registered trademark) W", Mw: 262). (B6): Toluene diisocyanate (TDI) (manufactured by Tosoh Corporation, product name "TDI", Mw: 174).
[0084] (Meth)acrylates having hydroxyl groups (C) (C1): 2-hydroxyethyl acrylate (manufactured by Nippon Shokubai Co., Ltd., product name "HEA"). Alcohols with one hydroxyl group (D) (D1): 2-Ethylhexyl alcohol (manufactured by Sankyo Chemical Industry Co., Ltd., product name "2-Ethylhexanol"). (Meth)acrylate (Y) (Y1): n-octyl acrylate (NOA) (manufactured by Osaka Organic Chemical Co., Ltd., product name "NOAA"). (Y2): Isobornyl acrylate (IBOA) (manufactured by Daicel-Allnex Co., Ltd., product name "IBOA-B"). Photopolymerization initiator (Z) 1-Hydroxycyclohexyl phenyl ketone (manufactured by IGM, product name "Omnirad (registered trademark) 184").
[0085] <Synthesis of urethane (meth)acrylate (X)> (Synthesis example 1 / (X-1)) Polyol (A1), polyisocyanate (B1) and (meth)acrylate (C1) were reacted in a molar ratio of 2.0:3.0:2.02. The actual amounts charged and reaction conditions are described below. A separable flask equipped with a thermometer and a stirrer was filled with 303.0 g of polyol (A1) (polyfarnesene glycol) and 800 ppm of dibutylhydroxytoluene (BHT). The internal temperature was set to 50°C, and the system was homogenized, after which 34 g of polyol (B1) (IPDI) was added. Then, 300 ppm of a urethane catalyst (dibutyltin dilaurate (DBTDL)) was added, and the internal temperature was set to 70°C to prepare a urethane isocyanate prepolymer. The completion of the reaction was confirmed when the isocyanate group concentration in the reaction liquid was equal to or lower than the theoretical NCO concentration (the same applies to other synthesis examples). In this example, the next operation was performed after confirming that the isocyanate group concentration in the reaction liquid was equal to or lower than the theoretical end point isocyanate group concentration (1.27 wt%). The theoretical NCO concentration (prepolymer) was calculated using the following formula (6). Theoretical NCO concentration = 42 × 2 × 100 ÷ (Mw of polyol × 2 + Mw of isocyanate × 3) (6) After confirming the isocyanate group concentration in the reaction solution, 12.4 g of (meth)acrylate (C1) was added to the reaction solution all at once. After aging for 2 hours, it was confirmed that the isocyanate group concentration was less than 0.05% by weight, and then the reaction was terminated to obtain urethane (meth)acrylate (X-1). The acryloyl group concentration of the obtained urethane (meth)acrylate (X-1) was 1,918 g / mol (0.52 mol / kg).
[0086] (Synthesis example 2 / (X-2)) A urethane (meth)acrylate (X-2) was obtained by the same synthesis procedure as in Synthesis Example 1, except that the polyol (A1), the polyisocyanate (B2) and the (meth)acrylate (C1) were reacted in a molar ratio of 2.0:3.0:2.02. The urethane (meth)acrylate (X-2) obtained had an acryloyl group concentration of 1,838 g / mol (0.54 mol / kg).
[0087] (Synthesis example 3 / (X-3)) A urethane (meth)acrylate (X-3) was obtained by the same synthesis procedure as in Synthesis Example 1, except that the polyol (A1), the polyisocyanate (B3) and the (meth)acrylate (C1) were reacted in a molar ratio of 2.0:3.0:2.02. The urethane (meth)acrylate (X-3) obtained had an acryloyl group concentration of 1,901 g / mol (0.53 mol / kg).
[0088] (Synthesis example 4 / (X-4)) A urethane (meth)acrylate (X-4) was obtained by the same synthesis procedure as in Synthesis Example 1, except that the polyol (A1), the polyisocyanate (B4) and the (meth)acrylate (C1) were reacted in a molar ratio of 2.0:3.0:2.02. The urethane (meth)acrylate (X-4) obtained had an acryloyl group concentration of 1,950 g / mol (0.51 mol / kg).
[0089] (Synthesis example 5 / (X-5)) A urethane (meth)acrylate (X-5) was obtained by the same synthesis procedure as in Synthesis Example 1, except that the polyol (A1), the polyisocyanate (B5) and the (meth)acrylate (C1) were reacted in a molar ratio of 2.0:3.0:2.02. The urethane (meth)acrylate (X-5) obtained had an acryloyl group concentration of 1,978 g / mol (0.51 mol / kg).
[0090] (Synthesis example 6 / (X-6)) A urethane (meth)acrylate (X-6) was obtained by the same synthesis procedure as in Synthesis Example 1, except that the polyol (A1), the polyisocyanate (B6) and the (meth)acrylate (C1) were reacted in a molar ratio of 2.0:3.0:2.02. The urethane (meth)acrylate (X-6) obtained had an acryloyl group concentration of 1,847 g / mol (0.54 mol / kg).
[0091] (Synthesis example 7 / (X-7)) Polyol (A1), polyisocyanate (B1), (meth)acrylate (C1) and alcohol (D1) were reacted in a molar ratio of 2.0:3.0:1.80:0.20. The actual amounts charged and reaction conditions are described below. A separable flask equipped with a thermometer and a stirrer was filled with 404.1 g of polyol (A1) (polyfarnesene glycol) and 800 ppm of dibutylhydroxytoluene (BHT). The internal temperature was set to 50°C, and the system was homogenized, after which 34 g of polyol (B1) (IPDI) was added. Then, 300 ppm of a urethane catalyst (dibutyltin dilaurate (DBTDL)) was added, and the internal temperature was set to 70°C to prepare a urethane isocyanate prepolymer. The completion of the reaction was confirmed when the isocyanate group concentration in the reaction liquid was equal to or lower than the theoretical NCO concentration (the same applies to other synthesis examples). In this example, the next operation was performed after confirming that the isocyanate group concentration in the reaction liquid was equal to or lower than the theoretical end point isocyanate group concentration (0.98 wt%). The theoretical NCO concentration (prepolymer) was calculated using the above formula (6). After confirming the isocyanate group concentration in the reaction solution, 10.6 g of (meth)acrylate (C1) and 1.3 g of alcohol (D1) were added to the reaction solution all at once. After aging for 2 hours, it was confirmed that the isocyanate group concentration was less than 0.05% by weight, and then the reaction was terminated to obtain urethane (meth)acrylate (X-7). The acryloyl group concentration of the obtained urethane (meth)acrylate (X-7) was 2,052 g / mol (0.49 mol / kg).
[0092] (Comparative synthesis example 1 / (X'-1)) Polyol (A'1), polyisocyanate (B1) and (meth)acrylate (C1) were reacted in a molar ratio of 2.0:3.0:2.10. The actual amounts charged and reaction conditions are described below. In a separable flask equipped with a thermometer and a stirrer, 307.8 g of polyol (A'1), 67.5 g of polyisocyanate (B1), and 800 ppm of dibutylhydroxytoluene (BHT) were charged. After stirring for 1 hour to homogenize the system, 300 ppm of urethane catalyst (DBTDL) was added. After confirming that the internal temperature had risen, the temperature was raised to 70°C and the mixture was aged for 3 hours to prepare a urethane isocyanate prepolymer. After confirming that the isocyanate group concentration in the reaction liquid was equal to or less than the theoretical value (2.27% by weight), 24.7 g of (meth)acrylate (C1) was added. The mixture was further aged for 2 hours to obtain urethane (meth)acrylate (X'-1). The acryloyl group concentration of the obtained urethane (meth)acrylate (X'-1) was 2,303 g / mol (0.43 mol / kg).
[0093] <Comparative synthesis example 2 / X'-2> The polyol (A'2), the polyisocyanate (B1) and the (meth)acrylate (C1) were reacted in a molar ratio of 2.0:3.0:2.10. The actual amounts charged and the reaction conditions are described below. Into a separable flask equipped with a thermometer and a stirrer, 269.1 g of polyol (A'2), 22.6 g of polyisocyanate (B1), and 129 g of (meth)acrylate (Y1) as a diluting monomer were charged. Furthermore, 800 ppm of dibutylhydroxytoluene (BHT) was charged relative to the reaction components other than (meth)acrylate (Y1). The internal temperature was raised to 50°C, and the mixture was stirred for 1 hour to homogenize the system, after which a urethane catalyst (DBTDL) (300 ppm relative to the reaction components other than (meth)acrylate (Y1)) was charged. After confirming that the internal temperature had risen, the temperature was raised to 70°C and the mixture was aged for 2 hours to prepare a urethane isocyanate prepolymer. After confirming that the isocyanate group concentration in the reaction liquid was equal to or less than the theoretical value (0.68% by weight), 8.3 g of (meth)acrylate (C1) was charged. After further aging for 2 hours, urethane (meth)acrylate (X'-2) was obtained. The ratio of (meth)acrylate (Y1) in urethane (meth)acrylate (X'-2) was 30% by weight ((X'-2) / (Y1)=70 / 30). The acryloyl group concentration of the obtained urethane (meth)acrylate (X'-2) was 1,374 g / mol (0.73 mol / kg).
[0094] <Comparative synthesis example 3 / X'-3> The polyol (A'2), the polyisocyanate (B1) and the (meth)acrylate (C1) were reacted in a molar ratio of 2.0:3.0:2.10. The actual amounts charged and the reaction conditions are described below. Into a separable flask equipped with a thermometer and a stirrer, 269.1 g of polyol (A'2), 22.6 g of polyisocyanate (B1), and 129 g of (meth)acrylate (Y2) as a diluting monomer were added. Furthermore, 800 ppm of dibutylhydroxytoluene (BHT) was added to the reaction components other than (meth)acrylate (Y2). The internal temperature was raised to 50°C, and the mixture was stirred for 1 hour to homogenize the system, after which a urethane catalyst (DBTDL) (300 ppm to the reaction components other than (meth)acrylate (Y2)) was added. After confirming that the internal temperature had risen, the temperature was raised to 70°C and the mixture was aged for 2 hours. After confirming that the isocyanate group concentration in the reaction liquid was equal to or less than the theoretical value (0.68% by weight), 8.3 g of (meth)acrylate (C1) was added. The mixture was further aged for 2 hours to obtain urethane (meth)acrylate (X'-3). The ratio of (meth)acrylate (Y2) in urethane (meth)acrylate (X'-3) was 30% by weight ((X'-3) / (Y2)=70 / 30). The acryloyl group concentration of the obtained urethane (meth)acrylate (X'-3) was 1,374 g / mol (0.73 mol / kg).
[0095] <Comparative synthesis example 4 / X'-4> The polyol (A'3), the polyisocyanate (B1) and the (meth)acrylate (C1) were reacted in a molar ratio of 2.0:3.0:2.10. The actual amounts charged and the reaction conditions are described below. A separable flask equipped with a thermometer and a stirrer was charged with 103.9 g of polyisocyanate (B1), 800 ppm of dibutylhydroxytoluene (BHT) relative to the reaction components, and a urethane catalyst (DBTDL) (300 ppm relative to the reaction components). The internal temperature was set to 50°C, and 308.2 g of polyol (A'3) was added dropwise over 4 hours. The reaction was carried out while gradually heating with cooling water so that the internal temperature did not exceed 80°C. After the end of the addition of polyol (A'3), the reaction was allowed to mature for 2 hours. After confirming that the isocyanate group concentration in the reaction liquid was below the theoretical value (3.18 wt%), 38 g of (meth)acrylate (C1) was added. The reaction was allowed to mature for another 4 hours, and urethane (meth)acrylate (X'-4) was obtained. The acryloyl group concentration of the obtained urethane (meth)acrylate (X'-4) was 4,209 g / mol (0.24 mol / kg).
[0096] The viscosity (60° C.) and Mw of the urethane (meth)acrylate obtained in each Synthesis Example and Comparative Synthesis Example were measured by the method described above. A summary of each example is shown in Table 1.
[0097] [Table 1]
[0098] [Examples 1 to 8 and Comparative Examples 1 to 7] The urethane (meth)acrylate (X) obtained in each Synthesis Example and Comparative Synthesis Example was mixed with (meth)acrylate (Y) as a viscosity adjusting monomer until the viscosity of the curable composition at 25°C became 600 mPa s or less. Then, 3% by weight of photopolymerization initiator (Z) was mixed with the total weight of the obtained mixture to obtain the curable composition of each example. The mixing ratios of components (X) and (Y) are shown in Tables 2 to 3. The viscosity of the curable composition obtained in each example was measured by the method described above. The appearance of the curable composition obtained in each example, and the transparency, heat resistance, and flexibility of the cured product were evaluated under the following conditions. The results are shown in Tables 2 to 3.
[0099] <Appearance Evaluation of Curable Composition> The curable composition obtained in each example was stored at −30° C. for 1 hour, and the presence or absence of turbidity or coloration due to crystallization or the like was visually evaluated according to the following evaluation criteria. (Evaluation criteria: appearance) Pass: Neither turbidity nor coloration was confirmed by visual inspection. Fail: Cloudiness and / or coloration was confirmed by visual inspection.
[0100] <Transparency evaluation of cured product> As shown in Fig. 1, a square frame (inner dimensions: 1.0 x 40 x 10 mm) was made of silicone rubber 12 on micro glass 11 (dimensions: 1.0 x 76 x 26 mm), and 1.0 g of curable composition 13 was dropped into the frame. After that, it was heated at 70°C, and when the surface became smooth, it was irradiated with ultraviolet light under the following conditions to cure, and a test piece of the cured product was obtained. (Ultraviolet irradiation conditions) Irradiation intensity: 120W / cm Irradiation distance: 10cm Conveyor speed: 5m / min Number of exposures: 2 Next, the transmittance was measured using a spectrophotometer (manufactured by Shimadzu Corporation, product name "UV-VISIBLE SPECTROPHOTO METER") with the microglass alone as a reference, and evaluated according to the following evaluation criteria. (Evaluation criteria: Transparency) Pass: The transmittance at 400 nm was 95% or more. Fail: The transmittance at 400 nm was less than 95%.
[0101] <Evaluation of heat resistance of cured product> A laminate 20 as shown in Figures 2 and 3 was produced and subjected to a heat resistance evaluation. Figure 2 is a top view of the laminate 20 as seen from directly above, and Figure 3 is a side view of the laminate 20. First, 0.50 g (±0.01 g) of the curable composition was accurately weighed and dropped onto the center of a glass plate 21 (1 mm thick, 5 cm square). A glass plate 21 of the same shape was then placed over the glass plate 21 to spread the curable composition in a circle (4 cm diameter), to obtain a laminate 20 in which the glass laminate 21 / curable composition 13 / glass laminate 21 were laminated in this order. Thereafter, ultraviolet light was irradiated from one side of the glass laminate 21 using a high-pressure mercury lamp (manufactured by Eye Graphics Co., Ltd.) under the following conditions to cure the curable composition 13. (Ultraviolet irradiation conditions) Irradiation intensity: 120W / cm Irradiation distance: 10cm Conveyor speed: 5m / min Number of irradiations: 8 times (4 times on each side) Next, the cured laminate 20 was stored in a small environmental tester (manufactured by Espec Corp., product name "SH-641") for 1000 hours at a temperature of 95° C. The shape of the laminate 20 after storage was evaluated according to the following evaluation criteria. (Evaluation criteria: heat resistance) Passed: There was no change in the shape of the laminate 20 after storage. Failed: The shape of the laminate 20 changed after storage (wrinkles occurred in the cured product and / or the glass plate was displaced).
[0102] <Flexibility evaluation of cured product> A square frame was made of silicone rubber on a glass plate (inner dimensions: 7×40×40 mm), and the curable composition was poured into the frame so that the void volume was filled. At this time, the curable composition was preheated and poured slowly to prevent air bubbles from being generated as much as possible. If air bubbles were generated in the curable composition, it was stored in an oven at 80° C. until the air bubbles were removed. The sample was heated at 80° C., and when the surface became smooth, it was irradiated with ultraviolet light under the following conditions to be cured. (Ultraviolet irradiation conditions) Irradiation intensity: 120W / cm Irradiation distance: 10cm Conveyor speed: 3.5m / min Number of exposures: 5 After curing, the cured product was removed from the silicone rubber, turned upside down, and further irradiated with ultraviolet light under the same conditions as above. This resulted in a test piece of the cured product with a thickness of about 7 mm. Then, using an automatic constant pressure loader (manufactured by Techclock Corporation, product name "GS-610"), hardness was measured in accordance with JIS K 6253. At this time, a type A hardness tester was used. At this time, the load was 500 g, and the load drop rate was 9 mm / s. After removing the load, the trace of the indenter's contact was observed and evaluated according to the following evaluation criteria. (Evaluation criteria: flexibility) Passed: There was no damage such as cracks on the part that came into contact with the indenter, or there was damage such as cracks on the part that came into contact with the indenter, but it recovered within 24 hours. Failed: The part that came into contact with the pin had damage such as cracks, and did not recover within 24 hours.
[0103] [Table 2]
[0104] [Table 3]
[0105] As shown in Table 2, the curable compositions of Examples 1 to 8, which satisfy the configuration of the first embodiment, were able to obtain curable compositions with low viscosity using a small amount of monomer (component (Y)), and also had good appearance. Furthermore, the cured products obtained from the curable compositions were excellent in transparency, heat resistance, and flexibility. On the other hand, as shown in Table 3, the curable compositions of Comparative Examples 1 to 4 containing urethane (meth)acrylates not containing structural units derived from farnesene were able to prepare low-viscosity curable compositions with a relatively small amount of monomer (component (Y)), and the appearance of the cured compositions was good, but the heat resistance or flexibility of the cured products was poor. The curable compositions of Comparative Examples 5 and 6 became cloudy and showed phase separation over time, so that it was not possible to measure the viscosity of the curable compositions or evaluate the cured products. As shown in Table 3, in Comparative Examples 5 and 6, when the amount of component (Y) was less than 30% by weight, the appearance was good, but the viscosity of the curable compositions was very high, and neither the viscosity measurement nor the evaluation of the cured products could be performed. Moreover, the curable composition of Comparative Example 7 containing only the urethane (meth)acrylate (X-1) and the photopolymerization initiator (Z) had a very high viscosity (25° C.) and was difficult to handle. From the above results, it was found that the curable composition according to the first embodiment is a low-viscosity active energy ray-curable composition, and can give a cured product having excellent transparency, flexibility, and heat resistance.
[0106] A non-limiting list of exemplary embodiments and combinations of exemplary embodiments of the present disclosure are set forth below. [1] A urethane (meth)acrylate (X) containing a structural unit derived from farnesene; a (meth)acrylate (Y) other than the urethane (meth)acrylate (X); and a photopolymerization initiator (Z). [2] The active energy ray-curable composition according to [1], wherein the urethane (meth)acrylate (X) is a reaction product of a polyol (A) containing a structural unit derived from farnesene, a polyisocyanate (B), and a (meth)acrylate having a hydroxyl group (C). [3] The active energy ray-curable composition according to [1] or [2], wherein the urethane (meth)acrylate (X) has a weight average molecular weight (Mw) of 5,000 to 30,000. [4] The urethane (meth)acrylate (X) is a reaction product of a polyol (A) containing a structural unit derived from farnesene, a polyisocyanate (B), and a (meth)acrylate having a hydroxyl group (C), The active energy ray-curable composition according to any one of [1] to [3], wherein the polyol (A) contains a diol represented by the following formula (I): [ka] (In formula (I), m and n each independently represent an integer of 1 to 7.) [5] A cured product of the active energy ray-curable composition according to any one of [1] to [4]. [6] A laminate comprising one or more layers selected from the active energy ray-curable composition according to any one of [1] to [4] and the cured product according to [5]. [Explanation of symbols]
[0107] 11: Micro glass 12: Silicone rubber 13: Active energy ray-curable composition 20: Laminate 21: Glass plate
Claims
1. A urethane (meth)acrylate (X) containing a structural unit derived from farnesene; a (meth)acrylate (Y) other than the urethane (meth)acrylate (X); and a photopolymerization initiator (Z).
2. 2. The active energy ray-curable composition according to claim 1, wherein the urethane (meth)acrylate (X) is a reaction product of a polyol (A) containing a structural unit derived from farnesene, a polyisocyanate (B), and a (meth)acrylate having a hydroxyl group (C).
3. The active energy ray-curable composition according to claim 1 or 2, wherein the urethane (meth)acrylate (X) has a weight average molecular weight (Mw) of 5,000 to 30,000.
4. the urethane (meth)acrylate (X) is a reaction product of a polyol (A) containing a structural unit derived from farnesene, a polyisocyanate (B), and a (meth)acrylate having a hydroxyl group (C); The active energy ray-curable composition according to claim 1 or 2, wherein the polyol (A) comprises a diol represented by the following formula (I): 【Chemistry 1】 (In formula (I), m and n each independently represent an integer of 1 to 7.)
5. A cured product of the active energy ray-curable composition according to claim 1.
6. A laminate comprising at least one layer selected from the active energy ray-curable composition according to claim 1 and the cured product according to claim 5.
Citation Information
Patent Citations
Farnesene polymers and liquid, optically transparent adhesive compositions incorporating them
JP2018527424A
Curable polyfarnesene-based compositions
JP2019501265A
Urethane (METH) acrylate, active energy ray-curable composition containing the same, and cured product thereof
JP2020041101A
Active energy ray-curable resin composition, adhesive composition and adhesive
JP2021123676A
Polyurethane resin for cosmetic, and cosmetic containing polyurethane resin for cosmetic
JP2022119195A